Book Store Robot - Shamsah, Ali (2021)
Universities Bookstores are usually crowded places. It is hard to control the processes of borrowing and buying books manually where they can be lost easily without knowing who took them and sometimes books can be returned without the knowledge of the administrator. This project is about designing a smart system to solve the problem mentioned above. The proposed system in this project will be a robot that can be used to fetch books from the shelves and return them back to their location. The bookstore administrator will be provided with an application on his PC or laptop to control the operation of the robot. This application will give the user the ability to control the robot manually or to determine the book name and if he wants it to be fetched or stored where the robot will go the book location depending on pre-assigned addresses on the administrator application. There will be a fetching area where the robot will automatically bring the book and put it there. The user application will communicate with robot wirelessly through Bluetooth connection. This robot will help in decrease the crowding in the book store and improve the process of fetching and storing books and make it faster, smoother, and more accurate.